2003
DOI: 10.1074/jbc.m206867200
|View full text |Cite
|
Sign up to set email alerts
|

Tetratricopeptide Repeat Motif-mediated Hsc70-mSTI1 Interaction

Abstract: Murine stress-inducible protein 1 (mSTI1) is a cochaperone that is homologous with the human Hsp70/ Hsp90-organizing protein (Hop). Guided by Hop structural data and sequence alignment analyses, we have used site-directed mutagenesis, co-precipitation assays, circular dichroism spectroscopy, steady-state fluorescence, and surface plasmon resonance spectroscopy to both qualitatively and quantitatively characterize the contacts necessary for the N-terminal tetratricopeptide repeat domain (TPR1) of mSTI1 to bind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 32 publications
(22 reference statements)
3
34
0
Order By: Relevance
“…6), TPR1 can discriminate effectively against the Hsp90 ligand and has no observable affinity for it. Also, for TPR1, residues beyond the carboxylate clamp binding ones, such as Lys-50, are crucial for discriminating against the noncognate ligand (40). The structure of the TPR2A-Hsp70 peptide complex explains why changes in the charged residues that predominantly interact with the peptide dicarboxylate clamp have similar effects whether TPR2A interacts with cognate or with non-cognate peptide ligands (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…6), TPR1 can discriminate effectively against the Hsp90 ligand and has no observable affinity for it. Also, for TPR1, residues beyond the carboxylate clamp binding ones, such as Lys-50, are crucial for discriminating against the noncognate ligand (40). The structure of the TPR2A-Hsp70 peptide complex explains why changes in the charged residues that predominantly interact with the peptide dicarboxylate clamp have similar effects whether TPR2A interacts with cognate or with non-cognate peptide ligands (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Hsc70 has been shown to play a critical role in the processing of voltage-gated K ϩ channels involved in the trafficking of axonal protein vesicles and the delivery of these channel-containing vesicles to the cell surface (59). Interestingly, recent studies on the binding domains within the Hsp70 and Hsp90 proteins have shown that there may be charge interactions between the various cargo proteins and chaperones (60,61), suggesting a possible role for the charged lysine residue at position 197 of hIK1 in chaperone-mediate protein trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, we identified Hop as a novel target for S100A2 and S100A6. Hop (11,33,34). Therefore, we speculated that these S100 proteins are able to compete with Hsp binding to Hop in intact cells.…”
Section: Discussionmentioning
confidence: 99%